Navigating Sunan Sittah in Exploring the Prophetic Style of Coping with Mental Health Issues: A Case Study on Sadness - Ali @ Mat Zin, Aizan (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2025)
This article explores the prophetic style of coping with mental health issues especially sadness by navigating sunnah. The Sunnah of the prophet are documented in the Quran and sunan sittah comprises of Sahih Bukhari, Sahih Muslim, Jami al-Tirmizi, Sunan Ibn Majah, Sunan Abi Daud and Sunan al-Nasai. There are many modern ways of coping with mental health issues, however Muslims are guided by the Prophet on how to live their life according to the revealed knowledge, in addition to acquired knowledge. One pertinent question is: how did the Prophet Muhammad P.B.U.H sustain his mental health despite misfortunes and obstacles in his daily life? The prophet is an exemplar to Muslims. Therefore, it is of paramount importance to gather the data in answering the research question. Data collection was done by using the method of documentation. The primary sources are the Quran and traditions. All collected data were categorized based on specific themes. Methods of inductive, deductive, comparative and contents analyses were rigorously implemented to generate novelties and findings. The findings exhibit that the prophetic styles are pragmatic and widely used in modern coping style. It seems that the prophetic style is relevant in the era of artificial intelligent. To conclude, this article proposes to all Muslims to learn and practice the prophetic style of coping mental health issues.